2007
DOI: 10.1007/s10936-006-9046-3
|View full text |Cite
|
Sign up to set email alerts
|

Metalinguistic Awareness and Reading Performance: A Cross Language Comparison

Abstract: The study examined two questions: (1) do the greater phonological awareness skills of billinguals affect reading performance; (2) to what extent do the orthographic characteristics of a language influence reading performance and how does this interact with the effects of phonological awareness. We estimated phonological metalinguistic abilities and reading measures in three groups of first graders: monolingual Hebrew speakers, bilingual Russian-Hebrew speakers, and Arabic-speaking children. We found that langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 25 publications
5
66
0
3
Order By: Relevance
“…In this context, phonological awareness of the first language was found to predict word identification and decoding skills in the second language (Cisero & Royer, 1995). Another research has found a relationship between the acquisition of phonological decoding in the mother tongue and reading acquisition in the second language (Ibrahim, Eviatar, & Aharon-Peretz, 2007). Phonological awareness was found to be a significant predicting factor of reading achievements in both languages, regardless of the nature or type of the mother tongue (Muter & Diethelm, 2001;Quiroga, Lemos-Britton, Mostafapour, Abbott, & Berninger, 2002).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…In this context, phonological awareness of the first language was found to predict word identification and decoding skills in the second language (Cisero & Royer, 1995). Another research has found a relationship between the acquisition of phonological decoding in the mother tongue and reading acquisition in the second language (Ibrahim, Eviatar, & Aharon-Peretz, 2007). Phonological awareness was found to be a significant predicting factor of reading achievements in both languages, regardless of the nature or type of the mother tongue (Muter & Diethelm, 2001;Quiroga, Lemos-Britton, Mostafapour, Abbott, & Berninger, 2002).…”
Section: Introductionmentioning
confidence: 81%
“…2) This is an extremely important research in the light of the findings of Ibrahim et al (2007) regarding differences in reading speed in Arabic and Hebrew among Arabic and Hebrew speakers (Ibrahim, Eviatar, & Aharon-Peretz, 2007). Ibrahim et al (2007) examined the utilization of the good phonological awareness among children Arabic mother tongue speakers compared to uni-lingual speakers of other languages (Hebrew speakers) and bi-lingual speakers (Hebrew and Russian speakers) (Eviatar & Ibrahim, 2001). They found that in reading, Arabic speakers do not utilize this advantage and that their performance in their language (Arabic) is lower (in terms of reading time and accuracy) than other lingual groups.…”
Section: Transfer Of Skills From One Language To the Othermentioning
confidence: 98%
See 2 more Smart Citations
“…Similar findings have emerged when comparing literacy achievements within Israeli society between Hebrew and Arabic speakers. Among Arabic speakers in Israel, some evidence indicates that reading rates are lower when reading their native Arabic (L1) as compared to reading non-native (L2) Hebrew (Ibrahim, Eviatar & Aharon-Peretz, 2007). Many researchers (e.g., Myhill, 2009) have suggested that some of these difficulties are attributable to the so-called "diglossia" phenomenon in Arabic (see below), first described by Ferguson (1959) to refer to the existence of a high-prestige literary language and a low-prestige spoken dialect(s).…”
Section: Reading Disabilities Among Arabic Speakersmentioning
confidence: 99%